Implementasi SK BAZNAS Nomor 13 Tahun 2025 tentang Nishab Zakat Pendapatan Berbasis Harga Emas: Studi di Pekanbaru - Aulia Jumaida; Sholihul Huda; Abd. Hadi (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
The enactment of BAZNAS Decree Number 13 of 2025, which determines the income zakat niṣāb based on gold-price qiyās, represents a significant development in Indonesia’s contemporary zakat governance. This study investigates the implementation of the policy in Pekanbaru City, explores donors’ perceptions, and evaluates its relevance from the perspective of Sharia Economic Law. A qualitative phenomenological case study was conducted using interviews, observations, and document analysis involving zakat administrators, muzakki, and Islamic economics academics. Data were analyzed using the interactive model of Miles, Huberman, and Saldana, while source and technique triangulation ensured data credibility. The findings indicate that zakat institutions have consistently implemented the standardized monthly niṣāb based on annual gold prices established by BAZNAS, supported by digital service innovations and adaptive communication strategies. Most donors perceive the policy as enhancing fairness, transparency, and legal certainty, although fluctuations in gold prices influence zakat calculations in certain cases. Institutional professionalism, public trust, and spiritual motivation were identified as key determinants of compliance with income zakat. From the perspective of Sharia Economic Law, the policy aligns with the objectives of maqāṣid al-sharī‘ah, particularly the protection of wealth (ḥifẓ al-māl), public welfare (maṣlaḥah), and legal facilitation (at-taysīr), providing empirical support for the development of contemporary zakat governance in Indonesia.